Teachers: the Second Parents of Students - อติธมฺโม, พระมงคลสุตาคม (Journal of Educational Review Faculty of Education in MCU, 2018)
Teachers and teaching professionals were regarded as the second parents of children. Teachers could be called as the second parents of students too since children and students were under the care of teachers from kindergarten until they completed their education. Again, children and students spent 6-8 hours or more a day in schools or in educational institutions with teachers. The teachers’ roles and responsibilities in teaching, training, caring and developing students could be compared to the parents’ duty. It can be said that teachers are the real second parents of children and students.